2010
DOI: 10.1136/jmg.2010.077883
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal respiratory cilia in non-syndromic Leber congenital amaurosis with CEP290 mutations

Abstract: These data provide the first clear demonstration of respiratory cilia ultrastructural defects in LCA patients with CEP290 mutations. The frequency of these findings in LCA patients along with the high expression of CEP290 in nasal epithelium suggest that CEP290 has an important role in the proper development of both the respiratory ciliary structures and the connecting cilia of photoreceptors. The presence of respiratory symptoms in patients could represent additional clinical criteria to direct CEP290 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 36 publications
(28 reference statements)
5
36
0
Order By: Relevance
“…We note CD in the respiratory epithelia also has been reported in patients with Leber congenital amaurosis (LCA), 32 a ciliopathy involving cone-rod dystrophy due to defects in the connecting cilium required for photoreceptor biogenesis. Patients exhibit “rarefaction of ciliated cells,” which also was observed in many of our heterotaxy patients with CD.…”
Section: Discussionsupporting
confidence: 53%
“…We note CD in the respiratory epithelia also has been reported in patients with Leber congenital amaurosis (LCA), 32 a ciliopathy involving cone-rod dystrophy due to defects in the connecting cilium required for photoreceptor biogenesis. Patients exhibit “rarefaction of ciliated cells,” which also was observed in many of our heterotaxy patients with CD.…”
Section: Discussionsupporting
confidence: 53%
“…Application of this model to all of the CEP290 patients described in the literature (table S2) (1419) again showed that predicted protein levels were robustly associated with disease severity ( P < 0.0001, Fisher’s exact test) (Fig. 2C).…”
Section: Resultsmentioning
confidence: 70%
“…None of the patients had optic atrophy or retinal coloboma, and none had any known nonocular medical conditions suggestive of a CEP290-associated multisystem ciliopathy syndrome (Joubert syndrome, Senior-Løken syndrome, Meckel-Gruber syndrome, or Bardet-Biedl syndrome). 2 Although subtle nonocular findings, such as abnormalities of respiratory cilia, have been associated with LCA-CEP290, 16,17 here we refer to LCA-CEP290 in our six patients as ''nonsyndromic'' to differentiate it from the four syndromes listed above.…”
Section: Methodsmentioning
confidence: 99%